Lapisan Perkerasan Komposit Batu Pecah pada Kontruksi Jalan Hutan - Rahardjo Rahardjo; S Suparto; S Sutopo (Jurnal Penelitian Hasil Hutan, 1987)
The use of pavement in Indonesian forest road construction at present is not common practice. Paving of logging roads is still considered too expensive, especially when its construction is not rational and effective. Information on pavement design especially with regard to its composition should help forest companies in solving their forest road construction problems.This investigation looks into the problem of finding the proper composition of crushed gravel and sand or rock dust for the construction of pavements. This kind of pavement is thought to have high shearing strength, stability and density.A series of laboratory test were conducted for this purpose, employing factorial analysis .A performance test in the field was conducted to compare with the Telford system using paired samples.The investigations revealed the following:- Crushed rock had significant influence on the shearing strength of the pavement. This material mixed with rock dust showed significant interaction.- Rock dust itself and water did not have significant effect on the shearing strength of pavement.- The use of water may help  facilitate the compaction process guiding the filler material into the voids among the crushed rock particles.- The proper composition turned out to be three units of crushed rock and two units of rock dust, resulting in a shearing strength of 0,226 kg/cm2.- Crushed rock composite made better pavement than the Telford system, resulting in lower settling of subgrade.- Based on the above, it is recommended to use a mixture of 2-3size crushed rock and rock dust in the proportion of 3 : 2 for pavement of forest roads, using smooth drum roller to obtain proper compaction.